(untitled) (Modern education and development, 2025)
English has become the dominant language of international communication, influencing various aspects of global culture. This article explores how English serves as a bridge between different nations in business, education, media, and technology. The widespread use of English in social media, entertainment, and diplomacy has contributed to cultural exchange and mutual understanding. However, the dominance of English also raises concerns about linguistic diversity and the potential decline of indigenous languages. The study highlights both the advantages and challenges of English as a global language and discusses its role in shaping modern communication and cultural identity.